A Novel Tool for Cost-Efficient Broadband Development through Infrastructure Sharing - Christos Bouras; Georgios Diles; Vasileios Kokkinos; Konstantinos Antonis; Leonidas Loukopoulos (The 20th IEEE Symposium on Computers and Communications, Larnaca, Cyprus, 2015)
Broadband is a public utility with positive effects on competitiveness, employment and growth. Although evidence shows that broadband development is increasing, this increment is not homogeneous between urban and rural areas. The main cause is the high cost for deploying next generation networks in rural areas, and especially the cost linked to civil engineering works. In order to overcome the investment challenges arising in the context of broadband deployment, the European Commission made mandatory the sharing of existing telecommunication and non-telecommunication infrastructures and facilities. This paper proposes and presents a novel tool that enables the estimation of the expected savings from exploiting existing infrastructures when deploying a broadband network. This is followed by a number of general principles and recommendations that policy makers and national authorities could embrace to diminish deployment costs and promote broadband deployment.